Perbandingan Pemasaran Digital Klub Sepakbola Lokal Dengan Internasional - Richard Andrew; Ian Nurpatria Suryawan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Digital marketing in local football clubs improve faster compare to their performance before pandemic. From their online shops, there are significant enhancement from the value to volume of transaction. Moreover, the researchers found out that a club can possess fans from various region and football itself are improving dramatically since Indonesia had a chance to run the U-17 Men’s World Cup 2023. This research want to compare Persija Jakarta, one of the best local club in Indonesia and FC Barcelona, one of the best international club in the world. The result of this research show that there are still a lot of spaces to develop the digital marketing of the club. This will not only make local club become famous in the nationwide but also in the Asian level. The implication of this research is that each club can boost their image by using the right digital marketing applications.